Smokers' preference for divorce and extramarital sex - Eiji Yamamura (Economics and Econometrics Research Institute (EERI), 2016)
It is known that smokers are more impatient than nonsmokers and tend to prefer current benefits. However, smokers' behavior in the marriage market has not as yet been well investigated. In this paper, individual-level data, which consist of over 10,000 observations from Japan, are used to examine how preferences for divorce and extramarital sex are different between smokers and nonsmokers. After controlling for various individual characteristics, the major findings are as follows: (1) smokers are more likely to have a positive view about divorce than nonsmokers; (2) smokers are more likely to have a positive view about extramarital sex than nonsmokers. These results were observed regardless of the individual's marital status. The findings here about smoker's preferences are consistent with the characteristics of smokers suggested in the literature. The findings suggest that whether one is a smoker presents important information in the marriage market, where information asymmetry can cause problems.
Keywords: J12; J19; I18; Z13; Z18; 330; smokers; divorce; extramarital sex; time preference; risk preference